Le Louvre. the palace & its paintings - Brisson, Dominique; Coural, Natalie; Reeunion des Mussees nationaux (France).; Montparnasse Multimedia (Paris : Montparnasse Multimedia: Rβeunion de Musβees Nationaux ; New York : distributed by BMG Distribution, 1995)
An interactive visit to the world's grandest museum.
Title from disc label.
"Selection #76896-40177-2."
"MAC/MPC CD-ROM."
System requirements: Multimedia PC or compatible with 386 SX or more powerful; 8 MB RAM; CD ROM drive; sound card; 256-color VGA monitor; mouse; Microsoft Windows 3.1 or later.
System requirements: LC III Macintosh; 3.5 MB RAM; CD ROM drive; 13 inch or larger 256-color VGA monitor; mouse; System 7 or later.
Keywords: Mussee du Louvre -- Catalogs -- Databases; Art -- France -- Paris -- Catalogs -- Databases; Architecture -- France -- Paris -- Databases; CD-ROMs.; Paris (France) -- Buildings, structures, etc. -- Databases